Asparagine Synthetase and Filamin A Have Different Roles in Ovarian Cancer - Zeng, Liang; Wang, Qiong; Gu, Congmin; Yuan, Li; Xie, Xiaohui; He, Lijuan; Chen, Kai; Tan, Pingping; Xue, Lei; Huang, Sanqian; Shi, Kun (Frontiers in Oncology, 2019)
Early-stage ovarian serous carcinoma is usually difficult to detect in clinical practice. The profiling of protein expression in high-grade serous carcinoma (HGSC) and low-grade serous carcinoma (LGSC) would provide important information for diagnoses and chemotherapy. Here, we performed proteomic profiling of specimens from 13 HGSC and 7 LGSC patients by iTRAQ. A total of 323 proteins that were differentially expressed were identified. After immunohistochemical confirmation of expressed proteins in 166 clinical tissues, asparagine synthetase (ASNS) and filamin A (FLNA) were selected for further functional study. Cisplatin-sensitive (CS; ASNShigh and FLNAlow) and cisplatin-resistant (CR; ASNSlow and FLNAhigh) SKOV3 and OVCAR3 ovarian cancer cell lines were used for subsequent in vitro and in vivo experiments. Notably, ASNS overexpression (ASNS+) or FLNA knockdown (shFLNA) enabled cisplatin-induced apoptosis and autophagy in CR cells. However, ASNS+ and shFLNA promoted and attenuated tumor growth, respectively. In CS cells, ASNS knockdown (shASNS) attenuated clonogenicity, cell proliferation, and the epithelial–mesenchymal transition, whereas FLNA overexpression (FLNA+) protected cells from cisplatin. In vivo, cisplatin resistance was attenuated in mice xenografted with ASNS+, shFLNA, or ASNS+-shFLNA CR cells, whereas xenografts of shASNS or FLNA+ CS cells exhibited resistance to cisplatin. Clinically, all HGSC patients (83/83) responded to cisplatin, while 6 in 41 LGSC patients exhibited cisplatin resistance. These findings identify ASNS and FLNA as distinct biomarkers for HGSC and LGSC, which may have potential value in the prognosis and clinical treatment of serous carcinoma.